Geophysical and Geotechnical Methods for Diagnosing Flood Protection Dikes - Fauchard, Cyrille (éditions Quae, 2007)
This book presents a three-phase methodology for the efficient diagnosis of â€œdry dikesâ€ (i.e. dykes built above normal water levels of the rivers that provide protection at time of flood). Although the principles of the method described herein were developed on dikes in France, they may be applied with confidence to flood protection dikes and levees in other countries around the world. Phase one of the methodology involves gathering as much information as possible about the dike from archive analysis, interviews with managers and inspections of the structures. This phase is essential in ensuring the high quality of the final diagnosis. The main aim of the second phase â€" the geophysical survey â€" is to divide up the dike into zones in order to identify sections of the structure that are vulnerable to irreversible damage during a flood because of their particular physical characteristics. The geophysical methods used must be capable of surveying over long distances and of revealing heterogeneities both within the dike and in its foundation. The third phase â€" the geotechnical investigation â€" consists of various tests and drillings that ascertain in situ the principal mechanical characteristics and properties of the materials that make up the structure. This guide is invaluable for anyone involved in dike safety